Intraoperative Optical Coherence Tomography Imaging in Corneal Surgery: A Literature Review and Proposal of Novel Applications. (11th September 2020) - Eguchi, Hiroshi; Hotta, Fumika; Kusaka, Shunji; Shimomura, Yoshikazu
Abstract : Intraoperative optical coherence tomography ( i OCT) is widely used in ophthalmic surgeries for cross-sectional imaging of ocular tissues. The greatest advantage of i OCT is its adjunct diagnostic efficacy, which facilitates to decision-making during surgery. Since the development of microscopic-integrated i OCT (MIOCT), it has been widely used mainly for vitreoretinal and anterior segment surgeries. In corneal transplantation, MIOCT allows surgeons to visualise structure underneath the turbid and distorted cornea, which are impossible to visualise with a usual microscope. Real-time visualisation of hard-to-see area reduces the operation time and leads to favorable surgical outcomes. The use of MIOCT is advantageous for a variety of corneal surgical procedures. Here, we have reviewed articles focusing on the utility of i OCT and MIOCT in penetrating keratoplasty, deep anterior lamellar keratoplasty, Descemet stripping automated endothelial keratoplasty, and Descemet membrane endothelial keratoplasty. The applications of MIOCT to corneal surgery in terms of surgical education for trainees, emergency surgery, and novel surgery are also discussed, with our cases performed using RESCAN ® 700.